KDRT DALAM HUKUM INDONESIA DAN PERANAN KETAHANAN KELUARGA GUNA MENEKAN KASUS KDRT - Sri Agustini (Ensiklopedia of Journal, 2023)
Various efforts have been made to foster happy families and anticipate various cases of domestic violence. The existence of domestic violence is a social fact of Indonesian family life, especially in West Sumatra. Currently, many women and children are victims of domestic violence. Domestic violence can be avoided by realizing family resilience. Family resilience will be realized with positive communication and commitment that is built between husband, wife and children who are bound in one household in accordance with Islamic teachings and applicable legal provisions. Proper understanding of each family member's role, rights and obligations will create a happy family and avoid domestic violence (KDRT).Keywords: Domestic Violence, Indonesian Law, Islamic Teachings, Family Resilience